Bioassay-guided isolation of antimycobacterial compounds from Aphloia theiformis (Vahl) Benn root ethanolic extract - Alphonce Ignace Marealle; Michael Qwarse; Ester Innocent; Ramadhani S.O. Nondo; Francis Machumi; Kerstin Andrae-Marobela; Matthias Heydenreich; Mainen Julius Moshi (Elsevier, 2023)
Background: Aphloia theiformis is used in Makete district, Tanzania, and other areas by HIV and AIDS patients as a weight loss remedy and for treatment of tuberculosis. However, there is no literature information on its antimycobacterial activity. Purpose: To evaluate antimycobacterial activity of A. theiformis root ethanolic extract and isolated compounds. Methods: The broth microdilution method was used to test the crude root ethanolic extract for activity against different non-pathogenic mycobacteria. Bioautography was used to identify the active constituents. Isolation of the active compounds was carried out using bioassay-guided fractionation. Chemical structures of compounds were established by comparison of their spectra with literature spectral data. The isolated compounds and some fractions were screened for activity against M. tuberculosis (MTB) subtype H37Rv and clinical isolates of MTB including strains resistant to rifampicin. Results: The 80% ethanolic extract of A. theiformis displayed activity against all non-pathogenic mycobacteria. The most active fraction was the ethyl acetate fraction from which two compounds were isolated; an epicatechin dimer; proanthocyanidin A2 (1) and tormentic acid (2) belonging to ursane pentacyclic triterpenoid. Compound (1) had MICs of 60.7 µM against Mycobacterium madagascariense and Mycobacterium indicus pranii and 255 µM against both standard MTB (H37Rv) and clinical isolate of rifampicin-resistant MTB. Conclusion: This study provides evidence in support of the use of A. theiformis extracts by traditional health practitioners for the management of tuberculosis. We recommend more studies to further assess efficacy and safety of the plant constituents using different models.